Pengaruh Prenatal Yoga terhadap Regulasi Emosi Pada Ibu Hamil di UPTD Puskesmas IV Dinas Kesehatan Kecamatan Denpasar Selatan - Ni Wayan Rika Parwati; Ni Made Ayu Yulia Raswati Teja; Putu Ayu Ratna Darmayanti (Universitas Malahayati Lampung, 2025)
ABSTRACT Pregnant women who experience hormonal changes cause them to have negative emotions, including jealousy and feeling more sensitive so that they need more support or attention. Psychological stress in pregnant mother is a serious health problem, however, it can be overcome with the right intervention. Prenatal yoga is a non-pharmacological intervention in overcoming psychological stress in pregnant women. To determine the effect of prenatal yoga toward emotional regulation in pregnant mother in the working area of Public Health Center IV South Denpasar. This study employed pre-experimental design with one group pre-test and post-test design. There were 37 respondents recruited as the sample using non-probability sampling with purposive sampling technique. The data were collected using self-completed questionnaire. Furthermore, the data normality test was analysed by using Shapiro Wilk test with the Paired T-Test analysis test. The finding showed that there was an increase in the average value of emotional regulation in pregnant mother before and after being given prenatal yoga with mean value before intervention was 42.03 and after intervention was 43.70. Thus, it could be stated that here was a significant effect of prenatal yoga on emotional regulation in pregnant mother with p-value of 0.001 (0.05). Prenatal yoga has been proven to have an effect on emotional regulation in pregnant mother in the working area of Public Health Center IV, South Denpasar. Keywords: Prenatal Yoga, Emotional Regulation, Pregnant Mother ABSTRAK Ibu hamil yang mengalami perubahan hormonal mengakibatkan mereka memiliki emosi negatif, diantaranya mudah cemburu dan merasa lebih sensitif sehingga memerlukan dukungan atau perhatian yang lebih. Tekanan psikologis pada ibu hamil merupakan masalah kesehatan yang serius, namun hal tersebut bisa diatasi dengan intervensi yang tepat. Prenatal yoga merupakan intervensi non farmakologis dalam mengatasi tekanan psikologis ibu hamil. Tujuan penelitian ini untuk mengetahui pengaruh prenatal yoga terhadap regulasi emosi pada ibu hamil di UPTD Puskesmas IV Dinas Kesehatan Kecamatan Denpasar Selatan. Penelitian ini menggunakan desain pre eksperiment, jenis penelitian one group pre post test design. Sampel sebanyak 37 responden. Teknik pengambilan sampel menggunakan Non-Probability Sampling dengan teknik purposive sampling. Metode pengumpulan data self-completed questionnaire. Alat pengumpulan data berupa kuesioner. Uji normalitas data yaitu uji Shapiro Wilk dengan uji analisa Paired T-Test. Terjadi peningkatan nilai rata-rata regulasi emosi pada ibu hamil sebelum dan setelah diberikan prenatal yoga dengan nilai mean sebelum intervensi (42,03) dan setelah intervensi (43,70). Ada pengaruh signifikan dari prenatal yoga terhadap regulasi emosi pada ibu hamil di UPTD Puskesmas IV Dinas Kesehatan Kecamatan Denpasar Selatan, dengan nilai p-value 0,001 (0,05). Prenatal yoga terbukti berpengaruh terhadap regulasi emosi pada ibu hamil di UPTD Puskesmas IV Dinas Kesehatan Kecamatan Denpasar Selatan. Kata Kunci: Prenatal Yoga, Regulasi Emosi, Ibu Hamil